Catalyst-free C-N bond formation under biocompatible reaction conditions - Goh, Jeffrey (2022)
A C-N bond formation reaction under biocompatible conditions for the amination of allenic ketone compounds to access a diversity of β-keto enamines is developed. This reaction is atom economical, green, and highly regioselective and works well with many structurally important amines such as amino sugar and amino acid esters or peptides. A wide array of β-keto enamines was obtained in modest to excellent yields with wide functional group tolerance using this protocol. A gram-scale synthesis of an anti-microbial agent was also realized using this strategy under green reaction conditions.